Gulf Oil in the Aftermath of the Iraq War : Strategies and Policies - The Emirates Center For Strategic Studies and Research (Abu Dhabi Emirates Center for Strategic Studies and Research, 2005)
On the new world oil map, the geographical focus of exploration and production is now shifting away from the Gulf to newer areas such as Russia, the Caspian basin, Venezuela and the West African rim. With global energy demand set to grow phenomenally, especially in Asia, and nations seeking to diversify and secure their oil supplies, this book analyzes the strategic investment and production choices needed to meet anticipated supply challenges.
Include Notes, Bibliography and Index
Keywords: Petroleum industry and trade -- Persian Gulf Region -- Congresses. -- Petroleum industry and trade -- Congresses. -- Petroleum industry and trade